'The English language enables me to visit my pain'. Exploring experiences of using a later-learned language in the healing journey of survivors of sexuality persecution. (April 2022) - Cook, Sally Rachel; Dewaele, Jean-Marc
Aims and objectives: This qualitative study explores the experience of using a later-learned language, English (ELX), in the therapeutic journey of refugee survivors of sexuality persecution to enhance understanding of the role of language in their rehabilitation. Design/methodology/approach: This is a multiple case study of three refugees, persecuted in their home country because of their sexual orientation, who are regular attendees of a therapeutic community, Room to Heal, based in London. A qualitatively driven mixed-method research design using Interpretative Phenomenological Analysis (IPA) and ethnography was employed. Data and analysis: Data were gathered through semi-structured interviews with the first author. They consisted of questions about the relationship between the participants' languages, emotions and sense of self. Findings/conclusions: Participants shared common positive experiences characterised by feelings of the ELX being a liberating tool that empowered them and enabled them to bear witness to their trauma, express their same-sex love more easily and be more self-accepting, and contributed to the (re)invention and performance of a 'new' self. Originality: The originality resides first in the unique profile of the participants – victims of persecution because of their sexual orientation; second in the unique context – a therapeutic community supporting refugees; and third in the methodology – a qualitatively driven mixed-method design combining IPA and ethnography. Significance/implications: The findings support an embodied perspective of languages and highlight the need for therapists to be aware of multilingualism and its effects. The reduced emotional resonance of a later-learned language may offer its users a way to access trauma and build a new self within the therapeutic process.